THE INFLUENCE OF CONSUMPTION VALUE ON CHOOSING SMARTPHONES AMONG COLLEGE STUDENT IN MANADO - Supit, Timmy; Saerang, David P.E; Pangemanan, Sifrid S. (Universitas Sam Ratulangi, 2014)
Smartphones are the common mobile phone as we know, also a new kind of technology that have a capability equal as computer to do every day job. Values from using smartphones influence college student to choose which smartphones to use as the best choice and the right tools to use. The purpose of this study to analyze influence of consumption value on choosing smartphones among college student in Manado. Where the independent variables are conditional value, functional value, emotional value, and epistemic value influence the consumer choice as the dependent variable. This research aim college student use smart phones in Manado. This study has been conducted through literature study as well as questionnaire administered survey. The research method associate with multiple regression analysis method with 100 respondent of different age groups, income and occupation have been consider for the survey. The collected data were analyzed to comply with the objectives and also to draw conclusions. Conditional value influence college student to choose smartphones especiallyÂ phone itself. Most of college student choose Iphone because its simplicity in extent, features that are used, and nature. Consequently, in general, the researcher believes that analysis of the demographic characteristics can explain the research findings of the influential factors and the ones insignificant to the decision making process.Â From this research are most of the consumers chooseÂ the smart phone based on conditional value concluded that consumption values do influence consumer choice within the college student that uses smart phone in Manado. Keywords: consumption values, consumer behavior, consumer choice